Bi-layer texture discriminant fast depth intra coding for 3D-HEVC - Zuo, Jiabao (2019)
3D-HEVC explores several new intra-frame depth coding tools to improve the coding efficiency, but at the price of high computational complexity, which hinders the practical applications of 3D-HEVC. Therefore, a bi-layer texture discriminant fast depth intra coding for 3D-HEVC is proposed in this paper. With a sum of gradient matrix (SGM), the texture complexity (TC) of current depth coding unit (CU) and its subblocks are calculated at once. The values of TCs indicate whether to split the depth CU further and skip unnecessary DMMs checking. The experimental results show that compared with the original 3D-HEVC, the proposed algorithm reduces the depth encoding time by 44.8%, and the average bit rate of the synthetic viewpoint is only increased by 0.38%, which outperforms the state-of-the-art fast 3D-HEVC algorithms.